Oxidative stress: role in pathogenesis of periodontal disease - RUBY RAMYA VINCENT; DEVAPRIYA APPUKUTTAN; P.S.G.PRAKASH; DHAYANAND JOHN VICTOR (International Journal of Pharma and Bio Sciences, 2017)
Oxidative stress is a phenomenon associated with pathogenesis of several inflammatory diseases including periodontitis. The pathological events leading to the destruction of the periodontium encompasses complex interactions involving an imbalance between oxidant and antioxidant enzymatic and non-enzymatic defense mechanisms. Reactive oxygen species (ROS) are generated predominantly by polymorphonuclear leukocytes (PMN) during an inflammatory response and are regarded as highly destructive in nature. Extensive research in this field of study has shown that the presence of ROS oxidation products, the elevated levels of iron and copper ions, which catalyze the production of most ROS, and the recognition of imbalance in the oxidant/antioxidant activity results in oxidative stress within the periodontal pockets. ROS are able to degrade the extracellular matrix components like proteoglycans leading to the fragmentation of its core protein, while glycosaminoglycans undergoes depolymerisation. The connective tissue metabolites that results from the degradation of the periodontal tissues are expressed in the gingival crevicular fluid (GCF) . This provides evidence for the role of ROS in tissue destruction associated with inflammatory periodontal diseases. In normal physiology, the multifunctional role of ROS purely depends on the delicate equilibrium between ROS production and the antioxidants. In pathologic conditions, when the equilibrium shifts in favor of ROS, either by a reduction in antioxidant defenses or an increase in ROS production or activity, Oxidative stress results. This paper aims to review the increasing body of evidence implicating Oxidative stress (OS) in the pathogenesis of periodontal tissue destruction.